Murder in the news an inside look at how television covers crime - Jordan, Robert H. Jr. 1943- (Prometheus Books, 2017)
"A veteran television news anchor provides a unique insider glimpse into the newsrooms of Chicago, revealing how decisions are made in selecting which murder cases receive TV coverage, how resources are allocated for live reporting, and how social media platforms change the dynamic of reporting the news."